Testing the Feasibility of Measuring Recovery in Adolescent Participants of an Alternative Peer Group: Lessons Learned and Next Steps. Issue 6 (November 2019) - Nash, Angela; Collier, Crystal; Engebretson, Joan; Cron, Stanley
The aim of this article is to report lessons learned from feasibility challenges faced in a mixed-methods study designed to test the feasibility of measuring recovery in participants of an Alternative Peer Group (APG). The APG integrates pro-recovery peers and social activities into clinical practice to engage adolescents in recovery. Though well established, APGs have never been tested. This study was one phase in a line of research that aims to develop an APG evidence base. The study used a mixed-methods design and naturalistic sampling of participants of one APG program. Repeated measures analysis with linear mixed models was planned to test the hypothesis that spending time in the APG builds recovery capital, resulting in progress in the processes of recovery, and improved symptoms. Semistructured interviews were conducted and framework analysis was used to explore feasibility challenges. Recruitment and retention challenges precluded meaningful measurement of change over time in recovery. Lessons learned from qualitative findings informed multiple strategies for revisions to strengthen future study protocols. Recruitment and retention of adolescents are common challenges that can threaten a study's validity. Researchers seeking to recruit and retain adolescents with SUD in longitudinal studies may benefit from strategies derived from this study.